2019
DOI: 10.3301/rol.2019.02
|View full text |Cite
|
Sign up to set email alerts
|

Water–budget as a tool to evaluate the sustainable use of groundwater resources (Isonzo Plain, NE Italy)

Abstract: Climate change and the necessity to preserve and provide good quality freshwater for human consumption has led researchers to study the aquifers of the Friuli Venezia Giulia Region (NE Italy) in more detail. Of particular interest is the crossborder Soča/Isonzo River, which contributed to the creation of a remarkable alluvial aquifer. Today more than 300.000 inhabitants are supplied by water withdrawals from AcegasApsAmga Hera Group and the IrisAcqua water companies, the water wells of which are located in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…As known for the western part of the hydrostructure (Civita et al 1995;Flora & Longinelli 1989;Doctor et al 2006), the level fluctuations observed in the cave are the result of several factors: the allogenic recharge by losses of the Isonzo River inside the Karst and autogenic recharge due to precipitation and consequently to the diffuse infiltration. The average contribution of Isonzo River to the aquifer recharge has been quantified in 10 m 3 /s (Urbanc et al 2012;Calligaris et al 2019a).…”
Section: Results Of Monitoringmentioning
confidence: 99%
“…As known for the western part of the hydrostructure (Civita et al 1995;Flora & Longinelli 1989;Doctor et al 2006), the level fluctuations observed in the cave are the result of several factors: the allogenic recharge by losses of the Isonzo River inside the Karst and autogenic recharge due to precipitation and consequently to the diffuse infiltration. The average contribution of Isonzo River to the aquifer recharge has been quantified in 10 m 3 /s (Urbanc et al 2012;Calligaris et al 2019a).…”
Section: Results Of Monitoringmentioning
confidence: 99%
“…The considerable water withdrawals and the rapid deterioration of groundwater highlighted the necessity of an integrated approach for the assessment of sustainable consumption and for planning of future uses. The waterbalance looks like the tool used to evaluate the available water resources and the future demand (Calligaris et al, 2010a(Calligaris et al, , 2010bHenriksen et al 2008;Kalf et al, 2005;Jukic´ et al, 2009;Sophocleous et al, 2004;Sorek et al, 2010;Zhou, 2009).…”
Section: Water Hydrogeological Budgetmentioning
confidence: 99%
“…On the western side of the study area, the Soča/Isonzo River (with its spring in the Slovenian Julian Alps), has an influent character toward the alluvial plain, which in turn recharges the Classical Karst hydrostructure with about 10 m 3 /s (Zini et al, 2013;Calligaris et al, 2019a). The third contribution is due to the effective infiltration estimated at 21 m 3 /s (Civita et al, 1995).…”
Section: The Classical Karst Regionmentioning
confidence: 99%
“…The contribution of the Notranjska Reka (Timavo Superiore) is estimated to be about 8 m 3 /s (Gabrovšek and Peric, 2006), and is extremely variable with almost negligible flow rates in low water conditions but particularly intense during floods. In the north-western sector between the towns of Merna and Sagrado, the aquifer of the Soča/Isonzo plain joins with the karst waters (Timeus, 1928;Mosetti and D'Ambrosi, 1963;Gemiti and Licciardello, 1977;Cancian, 1987;Doctor et al, 2000;Samez et al, 2005;Treu et al, 2017;Calligaris et al, 2018;2019a). In this area, especially during periods of low waters when the hydraulic gradient of the Classical Karst Region area is low, there is a significant transfer of water that recharges the hydrostructure with an estimated value of about 10 m 3 /s (Zini et al, 2013;Vizintin et al, 2018;Calligaris et al, 2019a).…”
Section: Hydrogeological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation